Dracocephalum ruyschiana L. (Ogres Kangari pie Ikšķiles) - Kupffer, Karl Reinhold (My University, 1923)
Nordischer Drachenkopf finden in sonnigers Abhang des Grandhügels am Ogre - Kanger bei Üxküll. /// Ruiša pūķgalve, atradne: liela kalna saulaina nogāze Ogres Kangaros pie Ikšķiles. /// Northern Dragon-head, deposit: sunny slope of the grand hill on the Ogre - Kanger near Ikskil. [Attēls no LU Muzeja kolekcijas Herbarium Balticum (RIG I); (BOT 2791_7)]
Keywords: Dracocephalum ruyschiana; ruiša pūķgalve; Nordischer Drachenkopf; northern Dragon-head; Kangari; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology